International Handbook of Primary Technology Education
X, 323 p.
Keywords: This international handbook offers an in-depth study of the development of primary Technology (or Design and Technology) education worldwide. It is unique in that it focuses on the way in which the building blocks for this subject have been established– providing much needed research and information for those involved with secondary education and beyond to draw on. The inclusion of Technology education into primary curricula has gathered momentum for the last two decades as its importance and relevance to children’s lives has been realised by educators. This handbook offers a detailed insight into the many and varied ways in which countries have incorporated the subject into children’s primary school experiences, and issues that have arisen during its implementation. The authors all work in the field of primary technology education and have been actively involved in curriculum development and research in their own countries. The first part of the book is devoted to the introduction, the development and implementation of Technology education into the primary curricula of countries worldwide. Reasons for this movement, successes and barriers to development are discussed and speculation about the future of Technology education is reflected upon. The second part of the book relates to issues that have arisen as the subject has grown over the last twenty years, and consideration needs to be given to these if future successes are to be achieved. Classroom practice including designing and ICT, teacher education, enterprise, sustainability and indigenous technology are all reflected upon and support the notion of technology as a valued and valuable part of the primary curriculum This book should be of interest to undergraduate and graduate students, practitioners, researchers, curriculum developers, policy makers and professional development providers who are involved with, and have an interest in, primary technology education worldwide.